Dynamic changes of land use/cover and landscape pattern in a typical alpine river basin of the Qinghai‐Tibet Plateau, China. (8th August 2021) - Li, Peijun; Zuo, Depeng; Xu, Zongxue; Zhang, Rui; Han, Yuna; Sun, Wenchao; Pang, Bo; Ban, Chunguang; Kan, Guangyuan; Yang, Hong
Abstract: Landscape heterogeneity is a comprehensive reflection of spatial patch and gradient, which is an important feature of landscape pattern. The China land use/cover dataset (CLUD) with 1 km spatial resolution was used in this study to investigate the dynamic changes of land use/cover in the Yarlung Tsangpo River basin (YTRB) of China from 1980 to 2015 through the land use transition matrix and dynamic degrees. The semi‐variogram model of the study area was constructed at different scales to determine the landscape characteristic scale of the YTRB. The traditional landscape index method and moving window method were used to investigate the watershed landscape pattern at the class and landscape levels, respectively. The results showed that the overall change in land use over the YTRB was not significant during the period 1980–2015, whereas the relative change in each type of land use was significant. Permanent glacier‐snow significantly degraded by 22.72%, while built‐up areas increased by 106.38%. The degree of the landscape fragmentation and diversity gradually increased from upstream to downstream. The unused land has the highest degree of fragmentation, and the agglomeration degree of urban land patches increased. The result of land use dynamic degree indicated that natural factors were the main causes of changes in land use during the first sub‐period 1980–2000, while human activities were the major drivers of changes in land use during the second sub‐period 2000–2015. The results can provide important information on the impact of regional development and environmental governance policies on the changes in land use/cover and landscape in Tibet.